2000
DOI: 10.1128/aac.44.9.2503-2506.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Conjugative mef Gene in Clinical Acinetobacter junii and Neisseria gonorrhoeae Isolates

Abstract: The mef gene, originally described for gram-positive organisms and coding for an efflux pump, has been identified in clinical isolates of Acinetobacter junii and Neisseria gonorrhoeae. These strains could transfer the mef gene at frequencies ranging from 10 ؊6 to 10 ؊9 into one or more of the following recipients: gram-negative Moraxella catarrhalis, Neisseria perflava/sicca and Neisseria mucosa and gram-positive Enterococcus faecalis. Three Streptococcus pneumoniae strains could transfer the mef gene into Eik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 23 publications
1
55
0
1
Order By: Relevance
“…Macrolide resistance in beta-hemolytic group G streptococci has resulted from horizontal transfer of mef genes among different species of streptococci, staphylococci, and enterococci, as well as among the beta-hemolytic group G streptococci themselves. Efflux of macrolides, mediated by mef genes, has been described mainly in various gram-positive cocci (5,7,8,11,12). From the available sequence information, it can be observed that the amino acid sequence corresponding to the mef gene (AY355407) of the beta-hemolytic group G streptococcus strain isolated from one patient shared more than 99% identity with that corresponding to a mef gene (U70055) from a strain of S. pyogenes (Fig.…”
Section: Vol 41 2003mentioning
confidence: 89%
“…Macrolide resistance in beta-hemolytic group G streptococci has resulted from horizontal transfer of mef genes among different species of streptococci, staphylococci, and enterococci, as well as among the beta-hemolytic group G streptococci themselves. Efflux of macrolides, mediated by mef genes, has been described mainly in various gram-positive cocci (5,7,8,11,12). From the available sequence information, it can be observed that the amino acid sequence corresponding to the mef gene (AY355407) of the beta-hemolytic group G streptococcus strain isolated from one patient shared more than 99% identity with that corresponding to a mef gene (U70055) from a strain of S. pyogenes (Fig.…”
Section: Vol 41 2003mentioning
confidence: 89%
“…Expansion of such competitive types has also been documented during distinct periods and in particular geographic regions (157). Frequent horizontal gene transfer seems possible (31,150), and in relation to the observations made for complement resistance, it may be postulated that other phenotypic traits could be acquired through cross-species gene acquisition. For instance, Bootsma et al (31) demonstrated that the barrier between M. catarrhalis and gram-positive microorganisms may be occasionally crossed by antimicrobial resistance genes.…”
Section: Conventional and Molecular Typing Systemsmentioning
confidence: 99%
“…All four of these sequences were identical to each other at the DNA and amino acid levels and identical with the GenBank U83667 and AF376746 sequences. Seventeen of the isolates in Table 3 hybridized with orf1 to orf8 from Tn1207.1, and seven of the isolates have been shown here or previously (5,6) to transfer the mef(A) gene to related and/or unrelated recipients. Whether these strains carry transposons similar to Tn1207.3, a recently described conjugal element from S. pyogenes (Santagati et al, 41st ICAAC), needs to be investigated.…”
Section: Mef(a) Gene Was Found In 20 Isolates Including Enterococcusmentioning
confidence: 99%
“…strain 130, and E. faecalis 2, as the donors. Matings were done as previously described (1,2,5,6,8,13). We also used the S. aureus 5 and S. intermedius 424 donors with Kingella denitrificans 87.023461 and Neisseria mucosa CTM1.1 as recipients as previously described (6).…”
Section: Bacterial Isolatesmentioning
confidence: 99%
See 1 more Smart Citation